2021
DOI: 10.1161/circ.144.suppl_1.11307
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 11307: Meta-Analysis Evaluating Dapagliflozin in Heart Failure Reduced Ejection Fraction: A Focus on Left Ventricular Remodeling

Abstract: Introduction: Through an unknown mechanism, anti-diabetic sodium-glucose cotransporter-2 inhibitors have been shown to be effective in patients with heart failure reduced ejection fraction (HFrEF). Specifically, dapagliflozin significantly decreased the risk of cardiovascular death and hospitalization for heart failure. However, the effects on left ventricular remodeling have not been well reported or analyzed. Methods/Results: We conducted a meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the real effect of SGLT2i on diastolic dysfunction is of debate. For example, Prasad et al’s meta-analysis concluded that there were no significant changes in diastolic or systolic function before and after dapaglifozin therapy against a substantial improvement in LV stroke volume [ 103 ]. In a retrospective study by Swathy et al, after one year of treatment with gliflozin, no effect of improvement of diastolic dysfunction was shown, but, on the contrary, there was a significant increase in LV mass [ 104 ].…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…However, the real effect of SGLT2i on diastolic dysfunction is of debate. For example, Prasad et al’s meta-analysis concluded that there were no significant changes in diastolic or systolic function before and after dapaglifozin therapy against a substantial improvement in LV stroke volume [ 103 ]. In a retrospective study by Swathy et al, after one year of treatment with gliflozin, no effect of improvement of diastolic dysfunction was shown, but, on the contrary, there was a significant increase in LV mass [ 104 ].…”
Section: Cardiac Remodelingmentioning
confidence: 99%